Bullying : experiences and discourses of sexuality and gender - Rivers, Ian.; Duncan, Neil, 1956- (Milton Park, Abingdon, Oxon : Routledge, 2013)
"Bullying: Experiences and Discourses of Sexuality and Gender provides a valuable insight into the experiences of young people and how bullying can impact upon them in the school environment. The book offers an introduction to the key issues associated with bullying on the grounds of sex and sexual orientation, and points to key policies and guidance on these difficult issues. With cutting-edge research and applied studies from leading academics and practitioners in the field, Bullying combines theory with suggestions for practical intervention for practitioners in education and social work. Chapter by chapter, the book strengthens the reader's knowledge base, and demonstrates how best to develop both academic and advocacy arguments to confront bullying, formulate intervention through examples of research findings, and recommend advice and guidance in professional contexts. Bullying offers multiple perspectives to challenge bullying related to gender, sexuality, and transgender status. The book includes the latest work on: - sexual bullying and the implications for policy and practice - sexual dimensions of cyberbullying - homophobia - sex differences in bullying - lesbian, gay, bisexual and transgender issues in educational contexts - planning and delivering interventions in schools. Bullying: Experiences and Discourses of Sexuality and Gender will appeal to education professionals, as well as researchers and postgraduate students in the social sciences, social work and educational and clinical child psychology"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Harassment in schools; Sexual harassment in education; Bullying in schools; Bullying in schools -- Psychological aspects; Electronic books